Dialogic Reading to Empower Executive Functions in Preschoolers - Costanza Ruffini; Silvia Spoglianti; Clara Bombonato; Silvia Bonetti; Maria Chiara Di Lieto; Chiara Pecini (Children, 2021)
Among the interventions recently developed to enhance Executive Functions (EFs) in preschoolers, Quincey Quokka’s Quest (QQQ) is an illustrated book proposing EF activities embedded within a shared reading framework (Howard et al., 2017). In the present study, the Italian version of QQQ (QQQIT) was tested in 20 typical developing 4–5 year old children. Standardized tests were used to assess EFs pre- and post- intervention. QQQIT was conducted once a week for 8 weeks in small groups. A positive trend was registered in QQQIT performances from the first to the last sessions and a significant improvement, in comparison to the control condition, was obtained in the Color and Form Game test. These results, supporting the feasibility of the QQQIT intervention and its efficacy in increasing shifting abilities, confirm the usefulness of ecological interventions to empower specific EF components in preschool contexts.